Mathematical Communication Skills and Mathematical Curiosity Students with intellectual disabilities: Bibliometric analysis - Arif Muchyidin; Nanang Priatna; Nurjanah Nurjanah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
This research aims to conduct a bibliometric analysis of the literature on mathematical communication abilities in children with intellectual disabilities. The primary focus of this research is to develop an overview of recent developments in the field and identify dominant research trends and areas requiring more exploration. Bibliometric methods are used to collect and analyze data from primary literature sources in articles and journals indexed by Scopus from 1990 to 2024, which are related to mathematical communication skills in children with intellectual disabilities. This research will also pay attention to the methods or approaches generally used in this research and evaluate the impact of this literature on developing understanding and intervention in improving the mathematical communication skills of children with intellectual disabilities. The result of this research was that no research discussed the relationship between children's communication skills, mathematical curiosity, and intellectual disability